2010
DOI: 10.1590/s1517-70762010000200025
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain curves for steel fiber-reinforced concrete in compression

Abstract: This paper presents a study on the compressive behavior of steel fiber-reinforced concrete. In this study, an analytical model for stress-strain curve for steel fiber-reinforced concrete is derived for concretes with strengths of 40 MPa and 60 MPa at the age of 28 days. Those concretes were reinforced with steel fibers with hooked ends 35 mm long and with aspect ratio of 65. The analytical model was compared with some experimental stress-strain curves and with some models reported in technical literature. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 6 publications
1
15
0
2
Order By: Relevance
“…De modo geral, e considerando a variabilidade observada nos ensaios, observa-se que a deformação de pico obtida experimentalmente ficou próxima dos valores recomendados na literatura. Com exceção do traba-lho de OLIVEIRA JÚNIOR et al [8], em todos os demais foi utilizada uma máquina de ensaio servocontrolada para determinação das curvas tensão-deformação. Isso mostra que a metodologia utilizada neste trabalho se mostrou eficaz para avaliar a deformação de pico do concreto sem fibras e do concreto reforçado com fibras.…”
Section: Curva Tensão-deformação à Compressãounclassified
See 1 more Smart Citation
“…De modo geral, e considerando a variabilidade observada nos ensaios, observa-se que a deformação de pico obtida experimentalmente ficou próxima dos valores recomendados na literatura. Com exceção do traba-lho de OLIVEIRA JÚNIOR et al [8], em todos os demais foi utilizada uma máquina de ensaio servocontrolada para determinação das curvas tensão-deformação. Isso mostra que a metodologia utilizada neste trabalho se mostrou eficaz para avaliar a deformação de pico do concreto sem fibras e do concreto reforçado com fibras.…”
Section: Curva Tensão-deformação à Compressãounclassified
“…Muitas dessas curvas são obtidas de regressões não lineares para obtenção de curvas empíricas com a descrição completa da curva tensão-deformação para o concreto. Neste sentido, citam-se os trabalhos de OLIVEIRA JÚNIOR et al [8], MANSUR et al [9]; BARROS e FIGUEIRAS [10]; e ARAÚJO [11]. Esse último autor realizou um trabalho com metodologia semelhante à deste artigo, contudo, utilizando uma máquina de ensaio servo-controlada, obtendo a equação empírica (1) para a curva tensão-deformação do concreto reforçado com fibras de aço:…”
unclassified
“…Liu [18] showed that the use of hooked-end steel fiber with the dimensions of 35 × 0.55 mm in concrete can control better its compressive failure (better performance/ductility). However, Oliveira Júnior et al [15] indicated that the compressive strength of unconfined concrete with hookedend steel fiber is comparable with that of the unconfined concrete without steel fiber. ey also found that the addition of steel fiber in concrete does not increase its compressive strength [15].…”
Section: Introductionmentioning
confidence: 98%
“…e stress-strain relationship of concrete should be discovered for its characteristics, since it can be used to derive its analytical approach or model. Several studies on the issue have been well addressed and studied previously [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. e studies resulted in the stress-strain relationships of normal-and high-strength concrete as well as the stressstrain relationships of steel fiber-reinforced concrete (SFRC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation